2006
DOI: 10.1111/j.1469-8986.2006.00403.x
|View full text |Cite
|
Sign up to set email alerts
|

The antisaccade task as a research tool in psychopathology: A critical review

Abstract: The antisaccade task is a measure of volitional control of behavior sensitive to fronto‐striatal dysfunction. Here we outline important issues concerning antisaccade methodology, consider recent evidence of the cognitive processes and neural mechanisms involved in task performance, and review how the task has been applied to study psychopathology. We conclude that the task yields reliable and sensitive measures of the processes involved in resolving the conflict between volitional and reflexive behavioral resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
410
2
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 460 publications
(452 citation statements)
references
References 154 publications
37
410
2
3
Order By: Relevance
“…Deficits sustaining attention and inhibiting context-inappropriate responses are well established in schizophrenia (38,11). Both types of deficits are promising endophenotypes for the disorder insofar as they are evident at illness onset, persist over the course of the disorder, and are found among unaffected relatives (39,40,41,12).…”
Section: Decreased Attention Fixation and Inhibitory Deficit In Schizmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficits sustaining attention and inhibiting context-inappropriate responses are well established in schizophrenia (38,11). Both types of deficits are promising endophenotypes for the disorder insofar as they are evident at illness onset, persist over the course of the disorder, and are found among unaffected relatives (39,40,41,12).…”
Section: Decreased Attention Fixation and Inhibitory Deficit In Schizmentioning
confidence: 99%
“…Multiple studies have reported elevated antisaccade error rates in schizophrenia patients (10,11,12) which are believed to represent disturbances in the prefrontally-mediated ability to voluntarily suppress prepotent responses (7,13). Patients followed longitudinally show a persistent elevation in antisaccade error rates over time, suggesting an enduring deficit of prefrontal functioning (14,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…A typical antisaccade task requires the participant to move their gaze in the opposite direction to a presented stimulus (Hutton & Ettinger, 2006). In order to do this successfully, participants must inhibit the prepotent oculomotor response of directing their gaze towards a newly presented stimulus.…”
mentioning
confidence: 99%
“…In the prosaccade paradigm, participants were required to perform simple saccadic eye movements toward a peripheral target when it appeared randomly in the right or left visual field (for a review, see Hutton & Ettinger, 2006). In visual word reading, participants were required to passively see the word stimuli or make orthography judgement tasks (for a review, see McCandliss, Cohen, & Dehaene, 2003).…”
Section: Methodsmentioning
confidence: 99%